Statistical Graphics in Czech Textbooks: A Comparative Content Analysis of Two Primary-Level Educational Areas - Tomáš Marek; Martina Maněnová (Revija za Elementarno Izobraževanje)
The aim of the article is to introduce an effective structural and functional model for the socialization and development of these children through group work, implemented in out-of-school education institutions (SFM). The study presents a comprehensive model comprising target, substantive, organizational, procedural, result-oriented, and analytical components. It outlines content and methodological support for socialization and development in various areas, such as naturalistic, tourist, local history, artistic, and aesthetic domains. It also highlights the essential spatial-subject, psycho-didactic, and social conditions required for an inclusive educational environment.